Evaluation of public transport: regional policies and planning practices in Sweden. Issue 1 (1st January 2017) - Johansson, Erik; Winslott Hiselius, Lena; Koglin, Till; Wretstrand, Anders
Abstract: This paper analyses regional public transport planning in Sweden. The aim is to provide an insight into how policy objectives are translated into action and to investigate how public transport measures are evaluated. The analysis is based on interviews with civil servants in five Swedish regions. Cost-benefit analysis is sparsely used (if ever) and the results further indicate that planning and evaluation of public transport is to a large extent centred around monitoring on-going trends, e.g. patronage and market share. Such information seems policy-relevant, i.e. is commonly asked for by the political level. The informants do ask for more knowledge regarding various effects (mainly social). However, it is less certain whether or not this knowledge would be used for economic evaluation. Regional and local public transport systems are complex, and intrinsically linked to land use and long-term regional ambitions. Instead of asking how public transport planning should be carried out, following CBA analyses, we should perhaps ask how the economic analysis could be tuned so that it becomes relevant for public transport planning. We foresee that the broader role of the public transport system will increase goal conflicts between, and within, authorities.